Safety of ultrasound-guided percutaneous renal biopsy-retrospective analysis of 1090 consecutive cases. - Hergesell, Olaf; Felten, Helmut; Andrassy, Konrad; Kühn, Karlwilhelm; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1998)
BACKGROUND: Ultrasound-guided renal biopsy with an automated spring-loaded biopsy device has become the standard method for kidney biopsy. Information on the success rate and safety of the routine use of this procedure from large series is not available. Such information is of interest for cost benefit considerations and for medicolegal purposes. We performed an audit of this procedure. SUBJECTS AND METHODS: From January 1993 to June 1997, 1090 percutaneous renal biopsies were performed in the renal units of Heidelberg (n = 557) and Karlsruhe (n = 533) using a spring-loaded biopsy device (Biopty; Radiplast AB, Uppsala, Sweden). After intensive local disinfection, biopsies were performed under local anaesthesia and direct visualization by ultrasound (Sonolayer SSH-140 A, Toshiba Inc., Japan). A puncturing adaptor was used (model UAGV 009 A, Toshiba, Japan). Of the 1090 biopsies 114 (10.4%) were performed on renal allografts and 976 (89.6%) on orthotopic kidneys. Biopsies were performed only if patients were strictly normotensive (<140/90 mmHg) and had normal coagulation parameters (PT, PTT, factor VIII, thrombocyte count, and bleeding time). All patients had been advised not to take aspirin or non-steroidal antiinflammatory agents for at least 5 days prior biopsy. We analysed (1) yield of diagnostically useful material, and (2) frequency of postbiopsy complications (e.g. macrohaematuria, haematoma, infections, and AV fistula). RESULTS: Except for one case requiring interventional radiology because of persisting blood loss and three cases requiring blood transfusions, no serious complications were seen in the 1090 consecutive renal biopsies, e.g. death, loss of kidney, life-threatening haemorrhage, or persisting haemodynamically relevant AV fistulae. The frequency of minor haematoma with an extension >2 x 2 cm, but no significant decrease of haemoglobin, was 2.2% (25/1090). Self-limited mild macrohaematuria occurred in 0.8% (9/1090). The incidence of small, haemodynamically irrelevant AV fistulae detected by Doppler ultrasound was 9% (48/533). Sufficient tissue for reliable histopathological diagnosis was obtained in almost all cases (1077/1090 = 98.8%). The median number of glomeruli per biopsy sample was 9 (range 1-37). CONCLUSION: If contraindications, especially high blood pressure and abnormal haemostasis, are respected, ultrasound-guided percutaneous renal biopsy with an automated biopsy device is safe. Skilled operators obtain satisfactory amounts of kidney tissue in almost all cases.